2012
DOI: 10.1021/ja300420t
|View full text |Cite
|
Sign up to set email alerts
|

Flexible, All-Organic Chemiresistor for Detecting Chemically Aggressive Vapors

Abstract: Chemiresistors made of thin films of single-walled carbon nanotube (CNT) bundles on cellulosics (paper and cloth) can detect aggressive oxidizing vapors such as nitrogen dioxide and chlorine at 250 and 500 ppb, respectively, at room temperature in ambient air without the aid of a vapor concentrator. Inkjet-printed films of CNTs on 100% acid-free paper are significantly more robust than dip-coated films on plastic substrates. Performance attributes include low sensor-to-sensor variation, spontaneous signal reco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
129
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 167 publications
(133 citation statements)
references
References 35 publications
4
129
0
Order By: Relevance
“…We chose cellulose-based paper as the substrate for the fabrication of chemiresistive sensors because it is a ubiquitous and inexpensive material that can be easily integrated into electronic devices (36). The compatibility of paper with several well-established surface-processing technologies [e.g., drawing (26), printing (22,23), metal evaporation (37), and chemical vapor deposition (38)] facilitates rapid and straightforward introduction of diverse electronic features onto the surface of paper, and integration into chemiresistive sensing devices. Previously, we demonstrated that weighing paper (i.e., highly compressed cellulose) was superior to other types of cellulose-based paper for making ammonia sensors from pristine SWCNTs by DRAFT (26); this demonstration further refined our choice of paper for this study.…”
Section: Design Of Devicesmentioning
confidence: 99%
See 1 more Smart Citation
“…We chose cellulose-based paper as the substrate for the fabrication of chemiresistive sensors because it is a ubiquitous and inexpensive material that can be easily integrated into electronic devices (36). The compatibility of paper with several well-established surface-processing technologies [e.g., drawing (26), printing (22,23), metal evaporation (37), and chemical vapor deposition (38)] facilitates rapid and straightforward introduction of diverse electronic features onto the surface of paper, and integration into chemiresistive sensing devices. Previously, we demonstrated that weighing paper (i.e., highly compressed cellulose) was superior to other types of cellulose-based paper for making ammonia sensors from pristine SWCNTs by DRAFT (26); this demonstration further refined our choice of paper for this study.…”
Section: Design Of Devicesmentioning
confidence: 99%
“…As a result, various methods have been developed for integrating CNTs into these electronic architectures [e.g., chemical vapor deposition (7,16), drop casting (17), spin coating (18,19), spray coating (20,21), inkjet printing (22,23), transfer printing (24,25), and mechanical abrasion (26)]. These methods provide a number of options for integrating CNTs into devices either as individual CNTs, highly aligned arrays of CNTs, or randomly oriented networks of CNTs (4,6,13,15).…”
mentioning
confidence: 99%
“…Many of the functionalities of these materials, such as their ultrahigh sensitivity, room-temperature workability, and high transparency, have already been improved. [8][9][10][11] However, like other wearable devices, flexible chemiresistors still have some shortcomings such as difficulty in controlling power usage because operation at lower power level for reduction in power consumption can cause degradation in device performance (i.e., slower response speed, lower resolution, etc.). [12,13] Therefore, in addition to device miniaturization methods to reduce power consumption, developing better sensing materials to enhance the sensing performance is also necessary for wearable electronics.…”
mentioning
confidence: 99%
“…The printed sensor concept has already been demonstrated by preparing, for example, ammonia gas sensors based on organic semiconductors, 15,16 and vapor sensors made from carbon-based materials such as reduced graphene oxide 17 or carbon nanotubes. 18 Unfortunately, many organic materials such as polyaniline 15 usually suffer from poor long-term stability and, as such, are not suited for reliable sensing for extended periods of time. Therefore, it is reasonable to explore inorganic materials, such as silicon, as alternative sensing materials.…”
mentioning
confidence: 99%